DIAGNOSTIC ACCURACY AND SAFETY OF ULTRASONOGRAPHY FOR INTESTINAL MALROTATION IN THE PEDIATRIC POPULATION - HANIF, N; SIDDIQUE, S; GORAYA, A; AARAJ, S; AKBAR, W; SIDDIQUE, S (Biological and Clinical Sciences Research Journal, 2024)
Intestinal malrotation is a critical condition in pediatric patients that requires accurate and timely diagnosis. Ultrasonography is a non-invasive imaging modality frequently used to diagnose this condition. Objective: To evaluate ultrasonography’s diagnostic accuracy and safety for detecting intestinal malrotation in pediatric patients. Methods: This retrospective study was conducted at Lahore General Hospital from January 2023 to January 2024. The study included children who underwent ultrasound for suspected malrotation during this period. Ultrasounds were performed by pediatric sonographers and interpreted by radiologists. The ultrasound examination was deemed indeterminate if normal anatomy was not delineated or the diagnosis was not confirmed. Data were analyzed to determine the sensitivity and specificity of ultrasonography in diagnosing intestinal malrotation. Results: Ultrasound examinations were performed on 230 patients for suspected malrotation. The mean age of the participants was 1.4 years. Among these, 61.7% (142) were neonates, with 36% (51/142) presenting on the first day of life. 218 (94.7%) patients had normal ultrasound findings, with no false-negative results reported. Malrotation was diagnosed through ultrasound in 7 (3%) patients, two of whom had associated malrotation. Five out of these seven patients were neonates. No false-positive results were reported after surgical confirmation. Additionally, 5 (2.17%) patients had indeterminate ultrasound findings. The sensitivity and specificity of ultrasonography for diagnosing intestinal malrotation were 100%. Conclusion: The study concludes that ultrasonography is a safe, accurate, and effective diagnostic tool for intestinal malrotation in pediatric patients. It is a feasible option for clinical practice due to its high diagnostic accuracy and non-invasive nature.